The Weakness of Will: The Role of Free Will in Treatment Adherence - Amdie FZ; Sawhney M; Woo K (Patient Preference and Adherence, 2022)
Fisseha Zewdu Amdie,1,2 Monakshi Sawhney,2 Kevin Woo2 1School of Nursing, University of Gondar, Gondar, Ethiopia; 2School of Nursing, Queen’s University, Kingston, Ontario, CanadaCorrespondence: Fisseha Zewdu Amdie, Email fmzewdu@gmail.comAbstract: Chronic disease prevention and management requires a lifelong commitment and adherence to lifestyle modifications, monitoring of symptoms, medication use, and other forms of therapy. Treatment adherence is a crucial and complex concept in patient care provision, and it requires the voluntary active involvement of patients for the best possible outcome. Multiple factors, which may or may not be under the patient’s control, can influence treatment adherence. However, adherence or non-adherence to a certain treatment is predominantly influenced by one’s sense of agency, values, beliefs, attitudes, and willpower. It is evident that mental states appear to influence patients’ decision-making, and the best treatment outcome occurs when a patient identifies their goals, needs, and desires and exercises their decision-making and free will during the course of receiving care. The role of healthcare providers is critical in promoting treatment adherence, thereby enhancing patient outcomes. Thus, this paper highlights the importance of promoting a sense of agency and integrating patients’ values, beliefs, attitudes, and intentions during the provision of healthcare. It is indispensable to recognize the individual’s ability and initiative to control and manage their illness in the face of challenging socioeconomic and cultural reality. On logical grounds, it is not enough to appreciate the value of free will and mental states, it is also essential to empower and cultivate an individual patient’s willpower to make a well-informed, free decision based on their mental state for the most optimal treatment outcomes.Keywords: free will, willpower, treatment, adherence, compliance